2022
DOI: 10.1111/dom.14841
|View full text |Cite
|
Sign up to set email alerts
|

Impaired awareness of hypoglycaemia: Prevalence and associated factors before and after FreeStyle Libre use in the Association of British Clinical Diabetologists audit

Abstract: BACKGROUNDFreeStyle Libre (FSL), intermittently scanned continuous glucose monitoring (isCGM), is associated with less biochemical hypoglycaemia in people with diabetes, lower HbA1c and diabetes-related distress. 1 Impaired awareness of hypoglycaemia (IAH), which affects 18%-33% of people with type 1 diabetes, 2 is the reduced ability to detect the symptoms of hypoglycaemia and is associated with a 6-fold increased risk of severe hypoglycaemia (SH). 3 Many of the studies of CGM have shown a reduction in rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The result presented here supports that the duration of diabetes and HbAc1 are significant predictors. The previous works demonstrated that individuals' subjective perception of hypoglycaemia and the intensity of their autonomous symptoms (especially trembling, hunger and sweating) progressively diminished with the duration of diabetes 33,34 . Specifically, the prevalence of IAH in people with diabetes increased from 3.0% for the duration of 2–9 years to 28.0% for the duration of at least 30 years 33 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The result presented here supports that the duration of diabetes and HbAc1 are significant predictors. The previous works demonstrated that individuals' subjective perception of hypoglycaemia and the intensity of their autonomous symptoms (especially trembling, hunger and sweating) progressively diminished with the duration of diabetes 33,34 . Specifically, the prevalence of IAH in people with diabetes increased from 3.0% for the duration of 2–9 years to 28.0% for the duration of at least 30 years 33 .…”
Section: Discussionmentioning
confidence: 98%
“…The previous works demonstrated that individuals' subjective perception of hypoglycaemia and the intensity of their autonomous symptoms (especially trembling, hunger and sweating) progressively diminished with the duration of diabetes. 33,34 Specifically, the prevalence of IAH in people with diabetes increased from 3.0% for the duration of 2-9 years to 28.0% for the duration of at least 30 years. 33 The group of patients with a longer duration of diabetes merits priority attention in future research and clinical practice.…”
Section: F I G U R Ementioning
confidence: 99%
“…CGM and intermittent retrospectively monitored CGM (Flash) with alarms are of proven benefit, the former in people with IAH and/or a history of severe hypoglycaemia, 21 the latter in a less selected population. 22 Replacing intermittent injections of insulin with continuous subcutaneous insulin infusion (pump) therapy also has older evidence to show benefit in reducing severe hypoglycaemia, 23 and the automated regulation of insulin delivery by pumps responding to data from linked CGM systems, including hybrid closed-loop systems, shows evidence of benefit. 24 Useful effects have been observed in populations at risk, 25,26 although protection from severe hypoglycaemia has not been seen in all studies, 27 and some have not focused on highrisk populations.…”
Section: The Management Of Iahmentioning
confidence: 99%
“…In recent years, intermittently scanned continuous glucose monitoring (isCGM) has emerged as a valuable tool for glycaemic management in T1D. [6][7][8][9][10][11] isCGM allows for real-time monitoring of glucose levels through a small sensor inserted under the skin, providing glucose readings at regular intervals without the need for frequent fingerstick blood glucose monitoring. isCGM has been shown to improve glycaemic control, reduce hypoglycaemic events, and enhance quality of life in individuals with T1D.…”
Section: Introductionmentioning
confidence: 99%